2014
DOI: 10.2478/sjce-2014-0020
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of Load-Bearing Components of a Cushioned Composite Piled Raft Foundation Under Axial Loading

Abstract: In the last decade piled raft foundations have been widely used

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Scholars have studied the effects of the elastic modulus and length of piles on the properties of composite foundations [ 1 , 9 , 10 ], while no studies have focused on the lateral earth pressure acting on the retaining structure adjacent to CFRLPs. To study the effect of the elastic modulus and length of flexible piles on the lateral earth pressure acting on the retaining structure, the elastic modulus of the flexible pile varies from 400–1200 MPa, the length of the flexible pile varies from 1–1.4 m, and the other parameters are the same as those above.…”
Section: Fem Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Scholars have studied the effects of the elastic modulus and length of piles on the properties of composite foundations [ 1 , 9 , 10 ], while no studies have focused on the lateral earth pressure acting on the retaining structure adjacent to CFRLPs. To study the effect of the elastic modulus and length of flexible piles on the lateral earth pressure acting on the retaining structure, the elastic modulus of the flexible pile varies from 400–1200 MPa, the length of the flexible pile varies from 1–1.4 m, and the other parameters are the same as those above.…”
Section: Fem Analysismentioning
confidence: 99%
“…The authors claimed that the length of the pile in the composite foundation has significant effects on the settlement of the foundation and that the greater the length of the pile, the less the settlement is. Sharma et al [ 10 ] numerically investigated the main factors influencing the settlement of composite foundations. The authors found that the settlement of the raft decreases with an increase in the cushion thickness.…”
Section: Introductionmentioning
confidence: 99%
“…In the finite element analysis of the pile-raft foundation, a solid element is used to simulate the pile, and the pile-soil interaction is, thus, considered by setting the interface elements [16][17][18]22]. The common interface model is the zero-thickness interface model proposed by Goodman et al [29].…”
Section: Solid Element and Interfacementioning
confidence: 99%
“…Schweiger et al [24], Tradigo et al [25], and Engin et al [30] verified the performance of single-pile foundations, pile group foundations, and pile-raft foundations simulated using the embedded pile element instead of the solid pile element. In the finite element analysis of the pile-raft foundation, a solid element is used to simulate the pile, and the pile-soil interaction is, thus, considered by setting the interface elements [16][17][18]22]. The common interface model is the zero-thickness interface model proposed by Goodman et al [29].…”
Section: Embedded Pile Elementmentioning
confidence: 99%
See 1 more Smart Citation